Hsa_circ_0001946 Inhibits Lung Cancer Progression and Mediates Cisplatin Sensitivity in Non-small Cell Lung Cancer via the Nucleotide Excision Repair Signaling Pathway - Huang, Ma-Sha; Liu, Jun-Yan; Xia, Xiao-Bo; Liu, Ying-Zi; Li, Xi; Yin, Ji-Ye; Peng, Jing-Bo; Wu, Lin; Zhang, Wei; Zhou, Hong-Hao; Liu, Zhao-Qian (Frontiers in Oncology, 2019)
Background: Despite great advances in the diagnosis and treatment of non-small cell lung cancer (NSCLC), early diagnosis remains a challenge because patients usually have advanced lung cancer at the time they are diagnosed. The limited efficacy of conventional chemotherapy is another major problem in the treatment of NSCLC. Based on a published set of sequencing data, we find that hsa_circ_0001946 is a circRNA molecule with a significantly different expression level in three cell lines (human normal lung fibroblasts cell line MRC-5, human NSCLC cell line A549, cisplatin-resistant cell line A549/DDP), NSCLC tissues and paired adjacent normal tissues. We believe that hsa_circ_0001946 may have an effect on the progression of NSCLC and its sensitivity to cisplatin. Methods: We focused on investigating the circular RNA, hsa_circ_0001946. RNA interference of hsa_circ_0001946 was carried out in A549 cell lines to determine the effect of reduced hsa_circ_0001946 expression on lung cancer progression and was analyzed by Cell Counting Kit-8 (CCK-8), 5-ethynyl-20-deoxyuridine, clone formation, Hoechst, wound healing, and transwell assays. The nucleotide excision repair (NER) signaling pathway was identified by Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Moreover, cellular responses to cisplatin were assessed through CCK-8 and flow cytometry assays. Western blot analysis and host-cell reactivation assay were used to determine the effect of hsa_circ_0001946 on NER signaling. Results: In this study, we found that the reduced expression of hsa_circ_0001946 promoted the viability, proliferation, migration, and invasion of NSCLC cells, as well as inhibition of cell apoptosis. Our findings suggest that hsa_circ_0001946 can affect the sensitivity of NSCLC cells to the chemotherapeutic drug cisplatin via modulation of the NER signaling pathway. Conclusions: Our study demonstrated the role of hsa_circ_0001946 in NSCLC pathogenesis, development, and chemosensitivity, and suggests that hsa_circ_0001946 may serve as a novel biomarker for the diagnosis and prediction of platinum-based chemosensitivity in patients with NSCLC.